ИНВЕСТИЦИОННАЯ ПОЛИТИКА И МЕХАНИЗМ РЕГУЛИРОВАНИЯ ИНВЕСТИЦИОННОГО ПРОЦЕССА (Journal of Economic Research & Business Administration, 2015)
This article is concerned with problems of the state investment policy and investment mechanisms. There is the research of the way to fulfill the investment policy.